2013
DOI: 10.3390/pharmaceutics5020261
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Absorption, Distribution, Metabolism, and Excretion of an Oral Amide Prodrug of Gemcitabine Designed to Deliver Prolonged Systemic Exposure

Abstract: Gemcitabine is an intravenously administered nucleoside analog chemotherapeutic agent. The ability to deliver this agent as an oral drug would allow greater flexibility of administration and patient convenience; however, attempts have been fraught with high first-pass metabolism and potential intestinal toxicity. Alternatively, an amide prodrug of gemcitabine (LY2334737) was discovered, which is able to avoid the extensive first-pass metabolism that occurs following administration of gemcitabine. Preclinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Collectively, these clinical studies indicate that the anti-tumor effect of gemcitabine is schedule dependent and that lower doses can be efficacious. Therefore, it could be advantageous to deliver gemcitabine in a manner where it can achieve prolonged systemic exposure, good efficacy with lower toxicity along with added flexibility of administration and greater patient convenience, such as using an oral formulation [ 48 ]. However, administering gemcitabine orally to patients has been limited by low oral bioavailability, high first-pass clearance, variable systemic exposures during dose escalation studies and observation of gastrointestinal toxicity including nausea, vomiting and diarrhea.…”
Section: Gemcitabine Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Collectively, these clinical studies indicate that the anti-tumor effect of gemcitabine is schedule dependent and that lower doses can be efficacious. Therefore, it could be advantageous to deliver gemcitabine in a manner where it can achieve prolonged systemic exposure, good efficacy with lower toxicity along with added flexibility of administration and greater patient convenience, such as using an oral formulation [ 48 ]. However, administering gemcitabine orally to patients has been limited by low oral bioavailability, high first-pass clearance, variable systemic exposures during dose escalation studies and observation of gastrointestinal toxicity including nausea, vomiting and diarrhea.…”
Section: Gemcitabine Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…It has been shown that human carboxylesterase-2 could hydrolyze LY2334737 to gemcitabine. 16,17 Alternatively, the 5 0 -position substitution of gemcitabine with a fatty acid (such as CP-4126) could lead to better permeability and reduced transport-related drug resistance, although the increased hydrophobicity might decrease the aqueous solubility of this type of prodrugs. 18 In the present study, the 5 0 -position substitution of gemcitabine was achieved with novel ether-lipid-like tail via a phosphate ester bond (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…24 The hydrolyzable amide modifications facilitate a slow release of gemcitabine, increasing its bioavailability and uptake while also providing resistance to enzymatic deamination. 25-32 In 2004, Immordono et al reported the increased anticancer activity of 4- N -stearoyl gemcitabine which was stable in plasma and showed an improved resistance to deamination. 28 Couvreur and Cattel developed the 4- N -squalenoyl gemcitabine prodrug (SQgem) as a chemotherapeutic nanoassembly that accumulates in the cell membranes prior to releasing gemcitabine 26 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%